Applying a healthcare model to Huntington's disease: the key worker approach - Wilson, Eleanor; Aubeeluck, Aimee; Pollock, Kristian (Mark Allen Healthcare, 2014)
This paper follows on from an overview of the literature and current policy for Huntington’s disease (HD) published by the BJNN (Wilson et al. 2014). The previous paper highlighted a paucity of knowledge in terms of best practice available for those commissioning services to draw upon when planning care of those with HD. This discussion paper draws on this literature base and findings from a recent longitudinal research study from Wilson’s (2013) unpublished PhD thesis (available online at http://etheses.nottingham.ac.uk/3487/) to suggest a model of care, which may provide some guidance.